Overview of the Level of Anxiety of Third Trimester Pregnant Women in Facing Labor at TPMB Elis Marlina - Ghina Nazla Hidayat; Widya Maya Ningrum; Kurniati Devi Purnamasari (Universitas Galuh, 2025)
The level of anxiety experienced by third trimester pregnant women in Indonesia, who have anxiety when facing the labor process, is 47.7% severe anxiety, 16.9% moderate anxiety, and 35.4% experience mild anxiety. The purpose of this study was to determine the description of the anxiety level of third trimester pregnant women in facing labor at TPMB Elis Marlina. This study uses a type of quantitative research with a descriptive design that aims to get an overview of the anxiety level of third trimester pregnant women in facing labor. The population in this study consisted of 30 third trimester pregnant women. The sample in this study used total sampling of 30 third trimester pregnant women. The measuring instrument used a questionnaire with direct data collection, data analysis using frequency distribution. The results of the study stated that of the 30 third trimester pregnant women, most of the 11 respondents (36.7%) experienced moderate anxiety, as many as 9 respondents (30%) severe anxiety, as many as 5 respondents (16.7%) mild anxiety, and as many as 5 respondents (16.7%) were not anxious. Based on the results of the study, it can be seen that the anxiety level of pregnant women at TPMB Elis Marlina is in the moderate category. It is expected to increase the provision of counseling to third trimester pregnant women about facing childbirth, or use other methods by holding pregnant women's classes to reduce anxiety facing childbirth.